Hydrothermal production and gel filtration purification of xylo-oligosaccharides from rice straw - Moniz, Patrícia (2017)
Hydrothermal treatment(autohydrolysis)isanadvantageousalternativetofractionatebiomassthat was notyetexploredforricestraw.Inthiswork,theprocesswasoptimisedandprovedtobehighly selective towardshemicellulose.Hydrolysatescontainingamixtureofoligomericcompounds(mainly xylo-oligosaccharides, XOS),couldbeobtainedunderrelativelymildoperationconditions(210 ◦C, log R0 = 3.59),yieldingamaximumof40.1g/100gofinitialxylan.TheproducedXOSwereseparated by molecularmassusinggelfiltrationchromatography(GFC).DifferentfractionsofpurifiedXOSwere obtained rangingfromsmallpolysaccharidesandhighDPoligosaccharides(DP ≥23), tomediumand low DPoligosaccharides(DP ≥3), andseparatedfractionsofby-products(aceticacid,furanderivatives and phenols)aswellasdi-,andmonosaccharides.GFCwasanefficientpurificationmethodenablingthe recovery ofinterestingcategoriesofXOSthatcanhavepotentialapplicationstothepharma,foodand feed industries